Evaluación de impactos a la salud del manglar en el municipio Guamá, Santiago de Cuba, Cuba - Cruz Portorreal, Yanet; Pérez Montero, Ofelia (Instituto de Ecología, A.C., 2017)
The aim of this study was to characterize the health status of mangroves in the Guamá municipality in Santiago de Cuba, Cuba. The methodology included the evaluation of the physiognomic aspects of the forest and its health index. Seventy-eight interviews were conducted with people of settlements neighboring the areas studied in order to assess the knowledge and community behavior regarding the mangroves. Fourteen environmental stressors were identified, among which are reported for the first time in Cuban studies, the sedimentation or accretion of sediments, as well as road construction, the advance of the agricultural frontier, cattle ranching, timber extraction and illegal logging. It is concluded that the health of the nine mangroves studied ranged from very high to low, according to the number of environmental stressors in each one. A total of 85% of environmental stressors in the area are of human origin, specifically related to socioeconomic development, while 15% are related to natural events. Finally, ecosystem health in the Guamá municipality is low, in spite of which they still maintain their environmental services.